Utilization of PID Controller to Optimize Energy Consumption in Hybrid Forced Convection Dryer - Brahmantya Aji Pramudita (JURNAL INFOTEL, 2024)
The drying process is essential in food processing, particularly for grains or beans. This process can influence the characteristics and quality of the dried material. However, the drying process needs massive energy. This condition can increase the cost of production. Therefore, optimizing energy is needed during the drying process. PID controller was proposed to be utilized in the dryer to maximize energy efficiency in this study. This method was implemented in forced convection and hybrid forced convection dryer. The temperature sensor was used as parameter control of the PID method to control the electric heater and exhaust fan. Moreover, PZEM-004T was used to measure the energy consumption. The objective of this study is to implement and fine-tune the PID controller to obtain the performance difference between two types of dryers, namely forced convection and hybrid forced convection. This will be achieved by collecting data on power and energy consumption. The results indicate that the hybrid dryer can significantly decrease power and energy consumption by 48.32% and 49.18%, respectively, compared to the forced convection dryer.